Evaluation of Health Resource Allocation Efficiency Based on Data Envelopment Analysis 2014–2018 in Two Dimensions of Time-Region - Lina Liu; Wei Xu; Yixuan Su; Xv Zhou (Discrete Dynamics in Nature and Society)
Since the new health care reform, China’s health care system has become increasingly mature and perfect, and the health awareness and needs of residents have also increased, which has raised higher requirements for the scientific understanding of the current status of health care resource allocation and making it achieve the goal of efficient operation. This paper evaluates the allocation of health resources in China from 2014 to 2018 in two dimensions: time and space by reviewing the China Health and Health Statistical Yearbook from 2014 to 2020, collecting data on the number of medical institutions, number of beds, per capita medical budget expenditure, number of consultations, and bed utilization rate during the study time interval, and analyzing them using data envelopment analysis. The results show that there are regional differences in the supply level of medical and health resources in China. Although the supply level is mainly on the rise, there are differences in the supply level of medical and health resources among provinces. The polarization phenomenon exists between eastern, central, and western regions, the urban and rural areas, the urban hospitals, and grassroots-level health care organizations.